2001
DOI: 10.1002/1096-911x(20010101)36:1<235::aid-mpo1057>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Late relapse and prognosis for neuroblastoma patients surviving 5 years or more: A report from the European Neuroblastoma Study Group ?Survey?

Abstract: The results of this study emphasise the importance of longterm follow-up of patients and the need for late monitoring of clinical trials in children with neuroblastoma. They also provide a baseline for comparison with future and hopefully more effective treatment programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 15 publications
0
24
0
3
Order By: Relevance
“…Some studies have shown that a more chronic course of neuroblastoma after failure of primary therapy seems to be associated with longer times of first remission 16 or older age at diagnosis. 17-19 Cotterill et al 20 identified late relapse in a small subset of high-risk patients; however, this study was unable to predict which factors influence long-term survival given the limited follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies have shown that a more chronic course of neuroblastoma after failure of primary therapy seems to be associated with longer times of first remission 16 or older age at diagnosis. 17-19 Cotterill et al 20 identified late relapse in a small subset of high-risk patients; however, this study was unable to predict which factors influence long-term survival given the limited follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…[31][32][33][34] Although one reason might be the detection of less extensive relapses through improved surveillance, as with 123 I-MIBG rather than 131 I-MIBG scan, another reason might be the identification of better treatments in recent years, including novel therapies with modest toxicity. Not only do the latter allow good quality of life, but it is plausible that in some patients, they will help achieve cure.…”
Section: Wwwjcoorgmentioning
confidence: 99%
“…Even though late relapse is uncommon, a small number of patients present with first disease recurrence after 5 years and on rare occasions beyond 10 years from diagnosis. Cotterill et al reported that amongst 406 patients who were in first remission five years from diagnosis, 3% subsequently relapsed and most late relapse patients had Stage 4 disease at diagnosis (Cotterill et al, 2001). …”
Section: Clinical Presentation Of Recurrent Nbmentioning
confidence: 99%
“…In these two studies, 28% to 36% of the patients with CNS recurrence had a lumbar puncture during diagnosis. As for late relapse beyond 5 years, a multivariate analysis of 422 patients demonstrated a relative risk of 10.5 for late relapse in patients >12 months with Stage 4 disease at diagnosis, and a relative risk of 4.2 for those with prior relapse (Cotterill et al, 2001). For patients who remained in first remission 5 years from diagnosis, the 10-year progression-free survival (PFS) for patients >12 months with Stage 4 disease at diagnosis was lower for other children (88% vs. 98%).…”
Section: Risk Of Disease Recurrencementioning
confidence: 99%
See 1 more Smart Citation